Acute eosinophilic appendicitis after generalized skin reaction due to unknown cause in a child: Case report and literature review - Maria Aggelidou; Katerina Kambouri; Maria Kouroupi; Dimitrios Cassimos; Soultana Foutzitzi; Savas Deftereos (Clinics and Practice, 2019)
Acute eosinophilic appendicitis (AEA) is a rare variant of appendix inflammation possibly linked to allergy. Histopathological evidence of eosinophilic infiltration of the muscularis propria and edema separating the muscle fibers is the gold standard for the diagnosis. Here, we report a case of a young boy with AEA following a skin reaction of possible allergic origin. A 6-year-old male was presented to the emergency department with a two-day diffuse abdominal pain and tenderness in the right lower quadrant. A possible allergic reaction had occurred five days before as a pruritic rash. There was no history of allergy and the stool examination was negative for parasites. The initial diagnosis was acute appendicitis, and appendectomy was performed. The histopathological diagnosis was AEA. Further studies on the proper diagnostic and treatment approach of AEA before surgery are required.